2021
DOI: 10.1200/jco.2021.39.15_suppl.9005
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in biomarker testing and clinical trial enrollment in non-small cell lung cancer (NSCLC).

Abstract: 9005 Background: Cancer racial disparities may exist at many levels in the health care system, from screening to timely diagnosis and treatments received, as well as clinical trial enrollment. This study investigated differences in black versus white race among patients with NSCLC undergoing biomarker testing and clinical trial enrollment in the US. Methods: This retrospective observational study utilized the Flatiron Health database, which includes longitudinal data of patients with advanced/metastatic NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Early evidence suggests that race may continue to play a role in access to equal care, and additional work is needed to continue to reduce the health care disparities that persist in the health care system. 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early evidence suggests that race may continue to play a role in access to equal care, and additional work is needed to continue to reduce the health care disparities that persist in the health care system. 14 …”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 , 13 There is emerging work that has begun to explore diagnostic testing in real-world settings, but gaps remain in the knowledge of current practices in biomarker testing and its utilization across community and academic practice settings. 5 , 14 , 15 This study, therefore, was designed to evaluate the utilization of single-gene and panel-based biomarker testing (by NGS) among patients with nonsquamous advanced or metastatic NSCLC in community and academic practice settings across the United States to quantify the rates of testing in current practice to inform the development of guidelines or initiatives to address gaps in the receipt of biomarker testing.…”
Section: Introductionmentioning
confidence: 99%
“…NGS testing may also improve clinical trial participation wich represents a very important pathway to access to innovative therapies. The same study previously cited showed that African American were also less likely to be treated in clinical trials (1.9% versus 3.9%) due to the lack of access to NGS testing 19 .…”
Section: Discussionmentioning
confidence: 63%
“…Our study did not assessed ethnic differences in terms of access to NGS testing. A recent study showed that African Americans were less likely to undergo NGS testing when compared to those who are Caucasian (39.8% versus 50.1%, p<0.0001) 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical delivery of precision oncology is however still uneven, with evidence suggesting that currently less than half of the targeted therapy eligible patients are ever receiving a targeted therapy. Challenges are complex and importantly include a still limited use of comprehensive next generation sequencing (NGS) diagnostics, with the lack of comprehensive tumor biomarker diagnostics in the USA often associated with marked racial and socioeconomical patient disparities [ 90 ]. Clinical trial awareness and participation are also major issues.…”
Section: Drivers Of Immune Responsesmentioning
confidence: 99%